SEBUAH TINJAUAN SISTEMATIS: PENGARUH PENGGUNAAN KONDOM TERHADAP PROGRAM “DUA ANAK CUKUP” DI INDONESIA - Yusuf Hanafi Lubis; Susilawati Susilawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
Government Regulation of the Republic of Indonesia Number 87 of 2014 concerning the development of occup-ation and Family Development, Family Planning, and Family Information System states that family planning (KB) programs are an effort to regulate the birth of children, distance and the ideal age of childbirth. The objectives of this study is to find out how much condom use in couples of childbearing age and strengthen the imple-mentation of the two-child program sufficiently in Indonesia. The research method used is to use systematic review by following the PRISMA checklist model in 2009 by search-ing the database with a publication period of 2018 - 2022 with keywords